(untitled) (Hungarian Journal of Industry and Chemistry, 2010)
The paper deals with the strains of removed chip and the root of the chip occurring in hard turning as finish manufacturing procedure, in case of orthogonal cutting. It examines the connections of thermal occurrence and plastic strains by the means of Finite Element Method simulation. For the simulation the data of experiments done previously were used. In the paper the change of the morphology of chip formation is compared depending on the cutting speed.